الإنتانات البولية عند الحوامل أهم الجراثيم المسببة وتحسسها للصادات - بلاش, عمر; عبد الرحمن, أحمد; لايقة, أيهم (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 300 حامل من مراجعات العيادة النسائية وقسم التوليد والأمراض النسائية في مشفى الأسد الجامعي في اللاذقية بين عامي 2004-2005 . وقد كان الهدف من هذه الدراسة مقاربة الإنتان البولي عند الحوامل من حيث نسبة حدوثه وأهم الجراثيم المسؤولة عنه وتحسس هذه الجراثيم للصادات الحيوية كما تمت دراسة بعض العوامل المؤثرة في حدوثه والوسائل المخبرية المستخدمة لكشفه. وقد خلصت الدراسة إلى النتائج التالية: كانت نسبة الإنتان البولي عند الحوامل 32.7% توزعت بين 24.3% للإنتان البولي العرضي 8.3% للبيلة الجرثومية اللاعرضية. لوحظ زيادة نسبة الإنتان البولي عند الحوامل مع التقدم بالعمر وتدني المستوى الاقتصادي والاجتماعي ووجود قصة إنتان بولي سابق. وجدت البيلة القيحية في معظم حالات الإنتان البولي العرضي في حين كانت غير موجودة في معظم حالات البيلة الجرثومية اللاعرضية. كانت حساسية اختبار استيراز الكريات البيض لكشف الإنتان البولي 72.5% أفضل من حساسية اختيار النتريت 41.8% . كانت العصيات الكولونية أهم سبب للإنتان البولي بنسبة 43.9% تلتها الكليبسيلا بنسبة 15.3% ثم العنقوديات سلبية المخثراز بنسبة 13.3% ثم المتقلبات بنسبة 11.2%. كان أفضل الصادات تأثيراً على الجراثيم سلبية الغرام سيفتازيدم ثم أميكاسين ثم جنتامايسين وكان أفضلها تأثيراً على الجراثيم إيجابية الغرام سيفالكسين ثم أميكاسين ثم جنتامايسين. في حين كان الأمبيسلين والأموكسيسيلين أقل الصادات تأثيراً على كلا النوعين من الجراثيم. The study included three hundred pregnant women of the visitors of the Gynecology Clinic and the Department of Obstetrics and Gynecology at AL-Assad University Hospital in Lattakia between 2004 - 2005. The aim of this study was to approach the urinary tract infection during pregnancy in respect of its incidence rate, the most important bacteria responsible for it, and their susceptibility to antibiotics. Moreover, the study examined some factors affecting the occurrence of urinary tract infection and the laboratory tests used to detect it. The study came up with the following conclusions: The urinary tract infection rate in pregnant women was 32.7 %, distributed between 24.3 % for symptomatic urinary tract infection and 8.3 % for asymptomatic bacteriuria. An increase of urinary tract infection rate was noticed in older pregnant women with low socioeconomic status and a past urinary tract infection history. Pyuria was present in most cases of symptomatic urinary tract infection; whereas it was absent in most cases of asymptomatic bacteriuria. The sensitivity of leukocyte esterase test for detecting urinary tract infection was 72% and better than the sensitivity of nitrite test 41.8%. E.coli was the most important cause of urinary tract infection at the rate of 43.9 % followed by Klebsiella at the rate of 15.3%, then coagulase negative Staphylococcus at the rate of 13.3 %, then Proteus at the rate of 11.2 % The most effective antibiotics on negative Gram bacteria were Ceftazidime, then Amikacin, then Gentamicin; and the most effective ones on Gram positive bacteria were Cephalexin, then Amikacin, then Gentamicin; whereas Ampicillin and Amoxicillin were the least effective antibiotics on both kinds of bacteria.